O diálogo da criança da educação infantil com a Ciência : olhares e entrelaçamentos a partir do Bosque da Ciência - Oliveira, Gerilúcia Nascimento de (2017)
The child’s dialogue with science: looks and meshes starting from “Bosque da Ciência” is a study with contribution to studies of childhood and in the foundations of Education in science which consisted of investigating how the Kindergarten Child builds its own concept of science starting from a visit to “Bosque da Ciência”, considering its mesh with the educational space and its relation to the peer culture. It aimed to understand the children’s participation in preschool educational contexts and in “Bosque da Ciência” Children are considered to be social actors in their contexts of life. Thus, it was performed a qualitative research in a Municipal Education Center, in Manaus – AM, with children in the second grade of preschool (5 – 6 years old) and their teacher. Participating observations, field records, audio records, filming and photos were performed in order to capture the child’s speech and understand how children build science. The study reveals that the science built by approaching the nature elements allowed the acquisition of new knowledge to be added to the existing one in a more systematized way, closer to the scientific concepts. Among these ones, it highlights the importance of body communication, of affection with their peers and with the environment around them, the childhood’s culture and the children’s cultural production as the ways they can participate in their educational and life contexts. These own modes of child participation with science refer us to build challenges in which they are protagonists in building science concepts, seeking possibilities to continue their experiences with an imaginative richness that derives from situations experienced by them. The children’s records were built through images (drawings) that pointed to an understanding of science as something possible and immediate, being marked by well-defined and specific traits starting from three visits to “Bosque da Ciência” which constituted source of information and the results discussed and completed in the analysis of visits. Keywords: Sociology of Childhood. Child. Culture of peers. Education in science. Preschool education.